MOTIVATION AND ENGAGEMENT: HOW COACHES CAN INSPIRE ATHLETES TO ACHIEVE THEIR GOALS AND IMPROVE PERFORMANCE (International Seven Journal of Multidisciplinary, 2022)
Motivation and engagement are foundational to athletic performance and long-term development in competitive sports. Coaches play a pivotal role not only in technical and tactical instruction but also in creating a motivational climate that fosters intrinsic motivation, emotional resilience, and team cohesion. Drawing on self-determination theory and transformational leadership models, this paper explores evidence-based strategies that coaches can employ to enhance athlete motivation and engagement. These include autonomy-supportive behaviors, mastery-oriented goal setting, emotional regulation training, and the development of strong coach–athlete relationships. Emphasis is also placed on the importance of adapting motivational techniques to individual and team contexts, taking into account age, experience, and cultural background. The findings highlight the central role of coaches in shaping both individual and collective outcomes in sport.